1994
DOI: 10.1111/j.1600-0714.1994.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) types 2 and 57 in oral verrucae demonstrated by in situ hybridization

Abstract: Twenty-one cases of verrucae vulgaris (oral warts) were investigated for human papillomavirus (HPV)-group specific antigen by immunocytochemistry and for HPV types 1, 2, 4, 6, 11, 16, 18 and 57 by DNA in situ hybridization with biotinylated probes. Twelve (57%) cases demonstrated the presence of HPV-group specific antigen. Fifteen (71%) cases showed the presence of HPV DNA, 13 of which (87%) demonstrated both HPV types 2 and 57 in the same cells and 2 of which (13%) demonstrated only HPV 2. Six cases were nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
2
24
0
2
Order By: Relevance
“…This infection often occurs on oral mucosa and the sites most involved are labial mucosa, with 55% of cases, the palate, jugal mucosa, gums, tonsils, uvula and roof of the mouth (9). Although the tongue is not commonly affected, the case presented both lesions on the tip of this organ.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This infection often occurs on oral mucosa and the sites most involved are labial mucosa, with 55% of cases, the palate, jugal mucosa, gums, tonsils, uvula and roof of the mouth (9). Although the tongue is not commonly affected, the case presented both lesions on the tip of this organ.…”
Section: Discussionmentioning
confidence: 91%
“…(21) Owing to the oncogenic role of certain types of HPV, the relation between this virus and carcinogenesis in oral mucosa is still controversial. Various studies have identified HPV in biopsies of oral SCC and VC (4,9,12). Among HPV types found in the oral mucosa, types 6 and 11 are more prevalent in benign lesions on the oral epithelium and types 16 and 18 more prevalent in malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto à distribuição histológica da casuística e à presença do HPV, verificamos (Tabela 3) o predomínio nos papilomas (100%), seguido das hiperplasias (95%) e finalmente pelos carcinomas (44,7%), que talvez possa ser explicado pelo aumento de práticas sexuais orais, e, em se tratando de lesões benignas (papilomas e hiperplasias), prevalecem em adolescentes e adultos jovens 12,13 . Ao lado disso, próteses mal-adaptadas podem determinar o sangramento de hiperplasias, apesar de sua menor freqüência quando desenvolvida a partir do trauma mecânico 11 .…”
Section: Discussionunclassified
“…Quanto à localização, houve o predomínio da língua (48,5%) em relação às demais, sendo o carcinoma epidermóide prevalente em 57,6% sobre a hiperplasia (30,3%) e o papiloma (12,1%) (Tabela 1). 12 . Nestes estudos, assim como no nosso, não houve diferenciação entre os papilomas e os condilomas ou as verrugas orais.…”
Section: Discussionunclassified
“…They observed a variation in the HPV detection rates from 43% to 100% in oral warts 29,31,32 . HPV prevalence in oral warts seems to be HPV 2, followed by the HPV 57, although more studies are necessary to identify the broad spectrum oral infectiosn caused by skin HPV types 20,33 .…”
Section: Oral and Oropharynx Common Wartmentioning
confidence: 99%